Factors affecting employees transfer of training among supporting staffs at Ministry of International Trade and Industry / Nor Farrah Waheeda Zulkiffly and Nurul Aini Roslinda Rosliza - Zulkiffly, Nor Farrah Waheeda; Rosliza, Nurul Aini Roslinda (Faculty of Business and Management, 2016)
In Malaysia, organizations implement various types of training programs to develop their employees’ skills. From the researcher’s perspective the training programs still lack of expertise in order to compete with the private organization for instance trainers’ lack of knowledge, training does not meet their main objective and insufficient cost. Therefore, this study attempts to study the factors that affect the transfer of training among the supporting staff at Ministry of International Trade and Industry (MITI). There are three independent variables which are training design, work environment and trainer characteristic whereas the transfer of training is the dependent variable. The research involved 196 of the supporting staffs at Ministry of International Trade and Industry (MITI) as the respondents. The result of the study shows that all the three independent variables influence the transfer of training. The strongest influence on transfer of training is from training design. Besides, the study also is expected to guide the top management of the organization to provide more effective training programs and better understand the concept of transfer of training after post-training.